2008
DOI: 10.1038/nnano.2008.211
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of near-ultimate strength for multiwalled carbon nanotubes and irradiation-induced crosslinking improvements

Abstract: The excellent mechanical properties of carbon nanotubes are being exploited in a growing number of applications from ballistic armour to nanoelectronics. However, measurements of these properties have not achieved the values predicted by theory due to a combination of artifacts introduced during sample preparation and inadequate measurements. Here we report multiwalled carbon nanotubes with a mean fracture strength >100 GPa, which exceeds earlier observations by a factor of approximately three. These results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
675
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,016 publications
(714 citation statements)
references
References 41 publications
29
675
2
8
Order By: Relevance
“…It was reported that defects introduced by oxidative pitting during composite preparation markedly reduce fracture strength, and extensive pitting leads to lower modulus [22,23]. Moreover, the other potential source of large defects of nanotubes was found by the use of sonication that caused strength underperformance [11]. In the present study, the direct physical homogenizing process in the presence of The dispersion state of SWCNTs in PVA matrix was directly observed by TEM.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…It was reported that defects introduced by oxidative pitting during composite preparation markedly reduce fracture strength, and extensive pitting leads to lower modulus [22,23]. Moreover, the other potential source of large defects of nanotubes was found by the use of sonication that caused strength underperformance [11]. In the present study, the direct physical homogenizing process in the presence of The dispersion state of SWCNTs in PVA matrix was directly observed by TEM.…”
Section: Resultsmentioning
confidence: 65%
“…This analysis gives effective nanotube strength of 175 GPa, which is relatively comparable to the highest measured strength of carbon nanotubes (ca. 110 GPa) [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To narrow the gap further, the structural parameters such as length, diameter and alignment of CNTs should be better controlled. For strength improvement, the intertube load transfer may be manipulated by already reported methods such as electron irradiation 31,32 , chemical treatment 33 and polymer impregnation [34][35][36] , forming primary bonds between CNTs, which are much stronger than Van der Waals interactions. For conductivity improvement, tube chirality should be particularly tailored 37 , and iodine doping 13,38 and metal coating 39,40 may be imposed.…”
Section: Discussionmentioning
confidence: 99%
“…The sp 3 C-C interlayer bonding has been experimentally observed in graphite and carbon nanotubes modified by electron irradiation 28 , femtosecond laser excitation 29 and thermal treatment 30 without chemical functionalization. In addition, quantum molecular dynamics calculation have evidenced the existence of interlayer sp 3 C-C bonding between graphene layers contained defects such as vacancies and interstitials 31 .…”
Section: Discussionmentioning
confidence: 99%